Microbial beginnings: determinants and disruptions of the neonatal microbiome - Bautista, Jhommara; López-Cortés, Andrés (Frontiers in Microbiology, 2025)
The perinatal period is a critical window in human development, during which the neonatal microbiome, shaped by maternal, environmental, and clinical factors, influences immune, metabolic, and neurodevelopmental processes. Early-life microbial assembly is an active, multisite, and functionally significant phenomenon, modulated by delivery mode, feeding practices, maternal microbiota, and antibiotic exposure. Vertical microbial transmission from the maternal gut, vagina, skin, and breast milk contributes to the colonization of the infant with taxa such as Bifidobacterium and Lactobacillus, while disruptions associated with cesarean section, formula feeding, or antibiotic use have been linked to persistent dysbiosis, impaired immune maturation, and increased risk of inflammatory, metabolic, and neurodevelopmental conditions. Recent studies also challenge the sterile womb paradigm, suggesting that prenatal microbial signals, whether microbes or metabolites, may reach the maternal–fetal interface and affect fetal programming. Furthermore, neonatal microbial profiles have been associated with later-life health trajectories, suggesting exploratory value as research biomarkers; however, these associations remain preliminary and are not validated for clinical application. In this review, we summarize and integrate evidence from multiomic, clinical, and experimental studies to describe the determinants, developmental dynamics, and health consequences of the neonatal microbiome. We also highlight emerging microbiome-targeted approaches, including maternal and neonatal probiotics, nutritional modulation, and systems biology frameworks, that may help to optimize early development and reduce disease risk. Understanding and modulating the perinatal microbiome represents a promising avenue for precision medicine and early-life prevention strategies.